Online Marketing sebagai Strategi Kualitas Layanan pada Perbankan Syariah - Ratri Nurina Widyanti; Mustaqim Pabbajah; Muh. Darwis (Al-Buhuts, 2022)
Online marketing strategies are a requirement for every institution in responding to the intensity of technology use in society. This paper aims to explain the need for online marketing to be implemented in Islamic banking as an effort to realize quality service for customers. The study is based on qualitative research with data sources in the form of observation, literature studies and documentation with descriptive analysis. Based on the analysis of the literature, it was found that Islamic banking needs to adapt to technological demands to socialize the concepts built on Islamic banks. Online marketing has an important role in providing information to the public regarding Islamic banking and its differences from conventional banks. In addition, online marketing is a strategy for providing quality service to customers and the public. Factors driving the success of Islamic banks in marketing products online are inseparable from; adequate infrastructure, mastery of digital literacy by human resources and innovative leadership. With an online marketing approach, besides being able to have implications for quality services, it can also be widely understood by the community effectively and efficiently. This paper suggests the need for responsive and adaptive Islamic banking to the increasingly rapid technological developments.